LANGUAGE PRODUCTION AND COMPREHENSION IN APHASIA - Friya Fadillah Setiawan (ReALL - Research on Applied Linguistics and Literature, 2023)
This research focuses on the characteristics and process of language production and comprehension in Broca aphasia sufferer. In this study, the researcher uses qualitative method. In addition, research data was collected from interview, observation, personal documents, and other notes with the researcher who became the research instrument. This research focuses on the characteristics and process of language production and comprehension in broca aphasia sufferer. From observation and interview, the researcher found five data included in the characteristics of broca aphasia sufferer, namely the existence of repeated gestures, frequent pauses when speaking, repetition, disfluency, and irregular speech rhythms. From this research, it can be concluded that people with broca aphasia have difficulty with expressing something even though they know what they want to convey to others. All problems experienced by broca aphasia sufferer lead to the characteristics of broca aphasia.